2013
DOI: 10.1016/j.micromeso.2013.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Use of bench-top NMR to measure the density, composition and desorption isotherm of C–S–H in cement paste

Abstract: Abstract1 H nuclear magnetic resonance (NMR), supported by a measurement of the degree of hydration using X-ray diffraction, has been used to fully characterise the nano-scale porosity and composition of calcium-silicate-hydrate (C-S-H), the active component of cement. The resultant "solid" density and composition are 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
137
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 18 publications
24
137
2
3
Order By: Relevance
“…The solid phase assemblages identified in the TGA results ( Figure 3) are similar to those identified by XRD (section 3.1); the peaks centred at 80-150°C in the TGA results indicate that >77% of the total mass lost in each sample is from interlayer and structurally bound water in C-(A-)S-H (noting that samples were freeze-dried and equilibrated to ~30% RH to remove the capillary and gel water [39]). The central positions of these mass loss peaks, and the total mass losses in each temperature range, do not vary systematically across the sample synthesis temperature range of 7-80°C, which suggests that the equilibration temperature is not the primary factor controlling the interlayer and structural water content of the C-(A-)S-H products formed here.…”
Section: Thermogravimetric Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…The solid phase assemblages identified in the TGA results ( Figure 3) are similar to those identified by XRD (section 3.1); the peaks centred at 80-150°C in the TGA results indicate that >77% of the total mass lost in each sample is from interlayer and structurally bound water in C-(A-)S-H (noting that samples were freeze-dried and equilibrated to ~30% RH to remove the capillary and gel water [39]). The central positions of these mass loss peaks, and the total mass losses in each temperature range, do not vary systematically across the sample synthesis temperature range of 7-80°C, which suggests that the equilibration temperature is not the primary factor controlling the interlayer and structural water content of the C-(A-)S-H products formed here.…”
Section: Thermogravimetric Analysissupporting
confidence: 58%
“…This analysis excluded contributions from Al(OH) 3 The calculated Ca/Si and Al/Si ratios of the C-(A- [50,51]), which suggests that only interlayer and structural water remains after the drying procedure used here (dried to RH ≈ 30% [39]). The use of a more severe drying procedure here than in a recent study of temperature effects on PC pastes [2] explains why the H 2 O/Si ratios of the low-Al C-(A-)S-H in that study were found to vary as a function of temperature and were significantly higher (2.28 ≤ H 2 O/Si ≤ 3.31) than those determined here.…”
Section: Preprint Version Of Accepted Article Please Cite As: Rj Mmentioning
confidence: 99%
“…The 15% RH threshold differs slightly from the reference point of 11% described above, which is based on an estimate of the RH at which the adsorbed layer on the pore surface is one molecule thick [37,38], not specifically on a threshold between gel pore and interlayer water removal. The existence of a threshold RH for interlayer water desorption is supported by some of the present authors' molecular-scale simulations [21,22], as shown in Figs. 3(a)-3(c) and by NMR experiments [31], as shown in Fig. 3(c).…”
Section: Interlayer Watermentioning
confidence: 81%
“…These pores are responsible for the hysteresis between drying and rewetting above 85% RH [17,34]. NMR experiments [31] show that 85% RH is a relevant threshold value for the capillary pores to be empty, and the Kelvin equation provides the corresponding pore width of 10 nm. The Kelvin equation also indicates that empty pores greater than 100 nm can fill only at RH very close to 100% in equilibrium conditions.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation